1990
DOI: 10.1007/bf01869106
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mutants with defects in two Ca2+-dependent K+ currents ofParamecium tetraurelia

Abstract: Paramecium tetraurelia possesses two Ca2(+)-dependent K+ currents, activated upon depolarization IK(Ca,d), or upon hyperpolarization IK(Ca,h). The two currents are mediated by pharmacologically distinct ion channel populations. Three mutations of P. tetraurelia affect these currents. Pantophobiac A mutations (pntA) cause calmodulin sequence defects, resulting in the loss of both Ca2(+)-dependent K+ currents. A second mutation, TEA-insensitive A (teaA), greatly enhances IK(Ca,d) but has no affect on IK(Ca,h). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This current activates slowly over a period of 0.5-1 s during hyperpolarization of the wild type (14). In rst however, it activates within milliseconds of hyperpolarizing the cell, and with an amplitude that is significantly increased compared with that of the wild type (36). Furthermore, the restless K+ current may be less dependent on Ca2+ for its activation than the wild-type counterpart (36): taken together, these observations suggest that rst produces an in vivo equivalent of a protease-digested channel.…”
Section: Genetic Dissection Of a Ca2+-dependent K+ Channelmentioning
confidence: 97%
See 1 more Smart Citation
“…This current activates slowly over a period of 0.5-1 s during hyperpolarization of the wild type (14). In rst however, it activates within milliseconds of hyperpolarizing the cell, and with an amplitude that is significantly increased compared with that of the wild type (36). Furthermore, the restless K+ current may be less dependent on Ca2+ for its activation than the wild-type counterpart (36): taken together, these observations suggest that rst produces an in vivo equivalent of a protease-digested channel.…”
Section: Genetic Dissection Of a Ca2+-dependent K+ Channelmentioning
confidence: 97%
“…Not only do the mutants lack the Ca dependent K+ current activated upon depolarization, but they also lack the hyperpolarization-activated Ca2+dependent K+ current. This finding raised the possibility that the two Ca2+-dependent currents reflect passage of K+ through the same channel protein, but the depolarization-and hyperpolarization-activated Ca2+-dependent K+ currents have since been shown to be pharmacologically distinct (36). The pntA mutations also affect the Ca2+-dependent Na+ current: this current is weakened by pntAl ( Fig.…”
Section: Calmodulin Is Required For Ca2+-dependent Ion Channel Activitymentioning
confidence: 99%
“… is probably a K + current ( I K ) through both voltage‐gated and Ca 2+ ‐activated K + channels, because both these channel types have been reported in Paramecium (Machemer ; Preston et al. ; Satow and Kung ) and we have previously documented Ca 2+ ‐activated K + channels in T. vorax (Grønlien et al. ).…”
Section: Resultsmentioning
confidence: 80%
“…6A). In Paramecium, the outward rectification is mainly due to Ca 2+ -activated conductances and is therefore secondary to Ca 2+ influx through voltage-gated channels (Preston et al 1990b;Satow and Kung 1980). This topic was not explored in detail in the present study, but we have previously demonstrated a pronounced Ca 2+activated K + conductance in T. vorax (Grønlien et al 2001).…”
Section: Membrane Rectificationmentioning
confidence: 99%
“…A solution containing 30 mM K' causes passive membrane depolarization that induces Ca2+ influx through a voltage-gated Ca2+ channel. Backward swimming thus reflects the kinetics of the Ca2+ channel [44]. As shown in Table 1, backward swimming elicited by 30 mM KC1 (1 mM CaCl,, 1 mM Hepes, 0.01 mM EDTA, pH 7.2) different from that of wild types were observed in three of the mutants.…”
Section: Behavioral Phenotypesmentioning
confidence: 88%